The PHEM-B toolbox of methods for incorporating the influences on behaviour into public health economic models - Squires, Hazel; Kelly, Michael P.; Gilbert, Nigel; Sniehotta, Falko F.; Purshouse, Robin C.; Garcia, Leandro; Breeze, Penny; Brennan, Alan; Gardner, Benjamin; Bright, Sophie; Fischer, Alastair; Heppenstall, Alison; et al. (BMC public health, 2024)
It is challenging to predict long-term outcomes of interventions without understanding how they work. Health economic models of public health interventions often do not incorporate the many determinants of individual and population behaviours that influence long term effectiveness. The aim of this paper is to draw on psychology, sociology, behavioural economics, complexity science and health economics to: (a) develop a toolbox of methods for incorporating the influences on behaviour into public health economic models (PHEM-B); and (b) set out a research agenda for health economic modellers and behavioural/ social scientists to further advance methods to better inform public health policy decisions.